Multifocal Epithelioid Hemangioma of the Penis in a 4-Year-Old Child: A Case Report. (May 2020) - Murshed, Khaled; Farghaly, Hanan
Abstract : Abstract: Epithelioid hemangioma (EH) is a rare benign vascular tumor which has wide morphological spectrum. In its typical forms, it is characterized histologically by lobular proliferation of vascular spaces lined by plump endothelial cells with variable inflammatory cell infiltrate in the background. They usually occur in middle-aged women and have predilection for the head and neck site, especially postauricular region. In this study, we report a case of a 4-year-old boy who presented with 2 red-raised skin lesions on the penis. Histopathologic examination revealed a dermal lesion composed of vascular spaces lined by epithelioid endothelial cells. The cells are bland with hobnail protrusions into the lumen. There is no cytological atypia or mitotic activity. The stroma is fibrotic with scant inflammatory cells. By immunoperoxidase stains, the tumor cells are positive with the vascular markers CD31 and CD34 but negative with the epithelial marker cytokeratin AE1/AE3. The diagnosis of multifocal EH was rendered. To the best of our knowledge, this is the first reported case in the English literature of multifocal EH developing in a child's penis.